Effect of online intervention based on life skills for mental health, self-efficacy and coping skills among Arab adolescents in the Klang Valley, Malaysia: A cluster randomised controlled trial protocol - Moreno-Peral, Patricia; Sherif, Yosra; Fattah Azman, Ahmad Zaid; Md Said, Salmiah; Siddiqah Alimuddin, Aishah; Awang, Hamidin; Mohammadzadeh, Marjan (Public Library of Science, 2024)
Background Migrant children and adolescents face a significantly increased risk of mental health issues. Focusing on this population’s mental health issues is fundamental and requires more attention to detect and reduce these burdens in adulthood. Nevertheless, life skills intervention can improve mental health. Its effects on Arab migrant adolescents have not been tested. Here, an evaluation protocol of the effect of an online life skills-based intervention for improving depression, anxiety, stress, self-efficacy, and coping skills among Arab adolescents in Malaysia will be examined. Material and methods This cluster randomised controlled trial (RCT) will involve 207 Arab students (14–18 years old) from 12 Arabic schools in the Klang Valley. The schools will be assigned randomly to an intervention (online life skills programme) or control group at a 1:1 ratio. The researcher will deliver eight one-hour sessions to the intervention group weekly. The control group will receive the intervention at the evaluation end. Both groups will complete assessments at baseline, and immediately and three months after the intervention. The primary outcome is anxiety, depression, and stress [Depression Anxiety and Stress Scale-21 (DASS-21)]. The secondary outcomes are self-efficacy (General Self-Efficacy Scale) and coping skills (Brief COPE Inventory). Data analysis will involve the Generalised Estimation Equation with a 95% confidence interval. P < .05 will indicate significant inter- and intra-group differences. Discussion This will be the first cluster RCT of an online life skills education programme involving Arab adolescent migrants in Malaysia. The results could support programme effectiveness for improving the participants’ mental health problems (depression, anxiety, stress), increasing their self-efficacy, and enhancing their coping skills. The evidence could transform approaches for ameliorating migrant children and adolescents’ mental well-being. © 2024 Public Library of Science. All rights reserved.